EVALUATING RETURN ON MARKETING INVESTMENT IN B2B DISTRIBUTION (Marketing Journal, 2026)
This article explores the evaluation of Return on Marketing Investment (ROMI) in B2B distribution companies. It examines the unique challenges of attributing marketing impact in multi -touch, long -sales -cycle environments, and highlights methodologies for c alculating ROMI at campaign, channel, and strategic levels. Emphasis is placed on integrated data infrastructure, analytical modeling, and cross - functional governance to optimize marketing spend, improve decision -making, and transform marketing from a cost center into a value driver. Practical examples and a maturity model illustrate implementation strategies.
Keywords: ROMI; B2B distribution; marketing effectiveness; trade promotion; CRM; multi -touch attribution; marketing analytics; resource optimization; sales performance; strategic investment